THE EFFECT OF LEADERSHIP AND TEAM WORK TOWARDS JOB SATISFACTION TEACHER IN STATE ELEMENRARY SCHOOL IN PASAR MINGGU SUB-DISTRIC SOUTH JAKARTA - Rini Indriati; Matin -; Neti Karnati (Peneliti.net, 2019)
This study aims to determine the effect of leadership and teamwork on teacher job satisfaction. To achieve this goal, this study uses a quantitative approach and data collection techniques using questionnaires. The survey was conducted from October 2018 to January 2019 involving 459 people from the SD Negeri Kecamatan Pasar Minggu South Jakarta. The sample in this study was randomly determined using the Slovin formula with 214 instrument trials. The findings from the results of this study indicate: first, the influence of direct leadership is positive and significant to the job satisfaction of the teachers with a path coefficient of 0.225. Second, there is a direct positive effect of teamwork on job satisfaction with path coefficients0,244. Third, there is a direct positive influence of leadership on teamwork with path coefficients 0.212 Based on the results of this study, teacher job satisfaction can be increased by the high atmosphere of leadership that is able to turn on the school atmosphere and influence followers. Team collaboration is used to increase job satisfaction, namely coordination, interpersonal activity, responsibility, support between individuals and collaboration.